Fundos para investimento social das organizações do terceiro setor - Gonçalves, Jaqueline Abrantes (2008)
Third sector organizations need to raise funds in order to guarantee their mission and the quality of services offered. Fundraising, whether through intersectoral partnerships or other sources of finance, enables their sustainability. This study profiles the sources of finance that provide financial resources to third sector organizations as well as the criteria behind the financing of social projects. The study assumed that was no bias in the choice of organizations benefited by the sources of finance. The study conducted was both qualitative and quantitative, and it covered 83 (eighty three) organizations that deal with social investment. From these, 48 (forty eight) financially support projects from third parties. The study identified the impossibility of setting the sources of finance in a single category. Due to lack of information, the inference that the sources always benefit the same organizations cannot be made. The number of sources has grown through the years, providing the creation of partnerships that generate innovative alternatives to sustain the third sector